2020
DOI: 10.3390/cancers12030653
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Clinical Correlation in Pediatric Medulloblastoma: A Cohort Series Study of 52 Cases in Taiwan

Abstract: In 2016, a project was initiated in Taiwan to adopt molecular diagnosis of childhood medulloblastoma (MB). In this study, we aimed to identify a molecular-clinical correlation and somatic mutation for exploring risk-adapted treatment, drug targets, and potential genetic predisposition. In total, 52 frozen tumor tissues of childhood MBs were collected. RNA sequencing (RNA-Seq) and DNA methylation array data were generated. Molecular subgrouping and clinical correlation analysis were performed. An adjusted Heide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 79 publications
(143 reference statements)
1
16
0
Order By: Relevance
“…Somatic DNA methylation status of 50 patients in our cohort (96.2%) have been examined using methylation arrays 16 . The sliding–window analysis of fluorescent intensities detected by the arrays offer information regarding somatic DNA amplifications and deletions 25 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Somatic DNA methylation status of 50 patients in our cohort (96.2%) have been examined using methylation arrays 16 . The sliding–window analysis of fluorescent intensities detected by the arrays offer information regarding somatic DNA amplifications and deletions 25 .…”
Section: Resultsmentioning
confidence: 99%
“…We then evaluated the independence of the gene signature-based score and a simple clinical risk stratification scheme proposed previously, where the patients were stratified into three groups, non-metastatic average risk (N = 25), non-metastatic high risk (N = 14), metastatic high risk (N = 13) 16 . Both the non-metastatic and metastatic high risk subgroups have significantly poorer overall survival than the non-metastatic average risk group (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not completely understood whether there are differences in genetic drivers of tumors between different racial ethnicities. Only two studies of MBs have been reported from Asian patients including a whole exome study of recurrent MB from only 17 pediatric patients in South Korea ( Phi et al, 2018 ) and a small SHH-subtype MB cohort from Taiwan ( Wu et al, 2020 ), however, a comprehensive analysis of Asian MB subgroups has not been conducted. In this study, we report the genomic landscape across a cohort of 89 MBs in the Han population from China.…”
Section: Introductionmentioning
confidence: 99%
“…Medulloblastoma (MB) is the most common primary malignant brain tumor in children and is currently treated on the basis of pathological and clinicoradiological risk stratification [1]. Despite progress in disease management, the overall survival remains dismal with 5 year survival rate around 70~75% [2]. Current therapeutic options have debilitating effects on developing children, highlighting the need for molecularly targeted treatments with reduced toxicity.…”
Section: Introductionmentioning
confidence: 99%